2010
DOI: 10.1007/s00134-010-1918-1
|View full text |Cite
|
Sign up to set email alerts
|

Hospital mortality is associated with ICU admission time

Abstract: Introduction Previous studies have shown that patients admitted to the intensive care unit (ICU) after “office hours” are more likely to die. However these results have been challenged by numerous other studies. We therefore analysed this possible relationship between ICU admission time and in-hospital mortality in The Netherlands. Methods This article relates time of ICU admission to hospital mortality for all patients who were included in the Dutch national ICU regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 25 publications
3
62
3
Order By: Relevance
“…Some authors have given [3][4][5] that the multidisciplinary ratio (medical staff, nursing, pharmacy, laboratory, diagnostic imaging, management etc.) and referral to medical specialists is hampered due to fewer professionals, providing a smaller number diagnostic investigations and therapeutic procedures based on evidence [3][4][5][6]10,[14][15][16] . Another factor that may have important association is related to the fatigue of professionals at night, and these are often the same professionals who worked during the day and stay at night, or who may already have come from other working hours; furthermore, the inversion of sleep-wake cycle can change and attention influence the procedures adopted 3,[17][18][19][20] .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…Some authors have given [3][4][5] that the multidisciplinary ratio (medical staff, nursing, pharmacy, laboratory, diagnostic imaging, management etc.) and referral to medical specialists is hampered due to fewer professionals, providing a smaller number diagnostic investigations and therapeutic procedures based on evidence [3][4][5][6]10,[14][15][16] . Another factor that may have important association is related to the fatigue of professionals at night, and these are often the same professionals who worked during the day and stay at night, or who may already have come from other working hours; furthermore, the inversion of sleep-wake cycle can change and attention influence the procedures adopted 3,[17][18][19][20] .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…3 A metaanalysis and a large national registry study of adult ICU admissions, each evaluating .130 000 admissions, demonstrated increased odds of death associated with weekend admission. 4,5 In the largest study in the pediatric ICU setting to date, which included .20 000 admissions to 15 PICUs from 1995 to 2001, nighttime admission was associated with increased odds of death. 6 Several smaller studies in PICUs found no difference in riskadjusted mortality for patients admitted during off-hours when compared with weekdays, 7-9 and 1 study found lower risk-adjusted mortality for admissions during off-hours.…”
Section: Resultsmentioning
confidence: 99%
“…The potential impact of transfer delays is underscored by several studies reporting that patients arriving at night or on the weekend had higher mortality and increased time to intervention. [19][20][21] However, comprehensive stroke centers have been shown to eliminate the weekend effect in stroke patients. 22 Although teleradiology technologies allowing remote review of medical images have existed for some time, little implementation of these methods has occurred in interhospital transfer.…”
Section: Discussionmentioning
confidence: 98%